China's Challenges in Moving Towards a High-Income Economy. - Song, Ligang. (China Update Series, 2021)
With its per capita income surpassing US10,000, China has now drawn up ambitious plans to further lift its income to the level of developed countries. Yet various constraints need to be overcome if China is to build on the achievements of the last 40 years and further boost its growth potential.